The quality of sour cherry fruits (Prunus cerasus L.), treated with chitosan solution before storage - Elena VASYLYSHYNA (Acta Agriculturae Slovenica)
The article shows the results of the research into marketability evaluation of sour cherry (Prunus cerasus L.) fruits, treated with chitosan solution. To achieve this goal, fruits were treated with 0.5 % or 1 % chitosan solution, and stored at 5 °C for 21 days. To assess the shelf life of fruit, physical and chemical parameters were determined: mass loss, reduction of sugar, titrated acidity and ascorbic acid content. Treatment with chitosan solution significantly reduced the mass loss, content of sugar, acids, ascorbic acid and respiration rate. The treatment with chitosan solution extended the shelf life and improved the quality of sour cherry fruit.